Chinese science diplomacy in Arctic climate governance based on a survey and interviews with Chinese scientists - Qingchao, Xu; Qingying, Xu (Polar Research Institute of China - PRIC, 2022)
Science diplomacy is attracting increasing attention in the international relations literature. This study investigates how Chinese scientists understand this term and explores China’s dynamic praxis in Arctic climate governance. It conducts a theoretical and practical examination of science diplomacy in terms of three dimensions—science in diplomacy, diplomacy for science, and science for diplomacy—thus achieving a high degree of consistency. A multi-method approach, combining qualitative and quantitative research methodologies and involving the adoption of a literature review, participant interviews, and questionnaires, is adopted. Data were collected from interviews with 16 Chinese scientists involved in Arctic climate governance and from 130 valid questionnaires collected from Chinese natural scientists working in the climate change field. Drawing on qualitative and quantitative findings, the study reveals that the three-dimensional framework of science diplomacy can provide insight into Chinese scientists’ understandings of the topic. In contrast to the participants’ vague theoretical responses, the outlines of China’s Arctic climate governance can be clearly identified within this framework. The study concludes by underlining the tension between theory and practice in terms of science diplomacy and highlighting the emerging challenges for China in developing its Arctic science diplomacy against the background of the COVID-19 pandemic and Russia-Ukraine conflict. Moreover, it is suggested that, to further develop China’s Arctic science diplomacy, it is vital to take account of the deficiencies in China’s science diplomacy. The study’s empirical results contribute to an understanding of the dynamic nature of science diplomacy in the Chinese context.